Ability level of eight from school children and their physical development - Kotlarski, Kazimierz (Anthropological Review, 1984)
The theoretical part of this article presents views referring to the interrelation between physical development and the level of mental ability. According to the first view able pupils are not so well physically developed as the remaining ones. According to the other view, able pupils are physically better developed (they are taller and heavier) than their less able peers. On the basis of our studies, it was found that the development indices of pupils are higher now than those obtained ten years ago, but there are no statistically significant differences in the development indices between able and unable pupils. These differences are not found in spite of the occurrence of rather significant differences in the income falling to one person and the living space falling to one person in the families of able and unable pupils. Further studies carried out on a greater number of groups differentiated both in reference to age and the socioeconomic status should bring a solution indicating in what degree the development indices (body growth and weight) are associated with the level of abilities and the socio-economic status.